Implementation Of Blue Economy And Green Economy To Support Sustainable Development In Islamic Economic Perspective (Study On Mangrove Tourism Petengoran Gebang Village, Teluk Pandan District, Pesawaran Regency) - Septiawan, Andika; Bahtiar , Muhammad Yusuf; Sisdianto , Ersi (Cattleya Darmaya Fortuna, 2025)
Mangrove forests are one of Indonesia's natural resources that are abundant in coastal areas. Mangrove ecosystems have many functions that are no less important, such as fisheries, coastal protection, recreation areas and so on. Currently mangrove ecosystems have been widely used to meet the needs of the community, such as settlements, aquaculture, industrial areas, agriculture and so on. The purpose of this study was to determine the illumination of Blue Ecocomy and Grand Economy in Petengoran mangrove forest in Gebang Village, Teluk Pandan Sub-District, Pesawaran Regency, and to determine the conservation efforts of Petengoran mangrove forest in Gebang Village, Teluk Pandan Sub-District, Pesawaran Regency. This research includes qualitative descriptive field research with literature study. Data retrieval using literature study, observation, and documentation. The Data obtained from the results of literature studies were then analyzed using descriptive analysis based on research objectives. The results showed that it was quite good after the mangrove forest conservation. The existence of mangrove forest tourism is very useful to increase the economy of the Gebang Village Community, mangrove hitan tourism involves communities around the coast to make efforts to improve mangrove forests because those directly related to the mangrove forest ecosystem are the people themselves.